STRATEGI PERANG SEMESTA MELALUI OPTIMALISASI NILAI-NILAI PANCASILA MENGHADAPI RADIKALISME PEGAWAI NEGERI SIPIL - tjandra ariwibowo; Lukman Yudho Prakoso; Helda Risman (Universitas Pertahanan Republik Indonesia (UNHAN RI), 2021)
The current dynamics of war development which tend to be asymmetric warfare, compel all strategic thinkers to face it. One of the asymmetric patterns of warfare after the second world war was religious radicalism. In previous periods, religious radicalism was promoted by groups from other countries to impose their interests through violent terror. To perpetuate its actions, this group popularizes its radical flow patterns throughout the world and all levels of society, including in the Republic of Indonesia. Many of its characteristics have been recognized by the government, which immediately conducts an evaluation to deal with them. The author observes this by examining Civilian Servants who are starting to be affected and the relationship patterns of their war strategies through optimizing Pancasila values in their training. The goal is that people understand the war that is happening and how to deal with radicalism through the inculcation of Pancasila values in training. The research method uses library research by studying various literature (books, references, previous research), information, data, and various documents. The end result has been implemented a universal war strategy through the formulation of Pancasila values in the basic training curriculum structure for Civilian Servant Candidates.